The Role Played by School Climate on School Effectiveness in Zimbabwean Secondary Schools: A Case Study of Nkayi South Circuit - Tshabalala, Thembinkosi; Ncube, Alfred Champion (Asian Journal of Social Sciences and Management Studies, 2014)
School environments vary greatly. Whereas some schools feel friendly, inviting and supportive, others feel exclusionary, unwelcoming and even unsafe. The feelings and attitudes are elicited by a schools environment are referred to as school climate. The effectiveness of an organisation depends to a large extent, on its climate. A leader’s decisions with regards to the structure of an organisation, leadership style and philosophy of leading, influence the climate of an organisation, which in turn, influences the effectiveness of the organisation. It is a necessary link between organisational structure and teacher attitude behaviour. Thus, a leader who is autocratic creates a climate which is coercive and powerlessness among staff members. In a school, these feelings are transferred to pupils and negatively affect effectiveness. Climate determines what staff members do, how they relate to each other and the quality of pupil achievement and other gains an organisation can achieve. It also affects such outputs as satisfaction, creativity and group decision-making. This article draws on a quantitative inquiry on the role played by school climate in promoting school effectiveness in Zimbabwean secondary schools using a sample of 200 teachers from a population of 650 teachers in Nkayi South Circuit in Matebeleland North in Western Zimbabwe. The sample had 110 females and 90 males. The research instrument used was the questionnaire. The study revealed that there was a very high correlation between a positive school climate and a school’s high pass rate standards. The findings also revealed that poor result were closely linked to a negative school climate. The study recommends that school heads should create a conducive school climate to enhance the effectiveness of their schools. Furthermore, adequate resources should be provided in rural schools in order to create an enabling climate for high student achievement.